STUDY OF IMPORTANCE OF KAKSHADHARA MARMA W. S. R TO ERBS PALSY - Umakant Mangrule, *Pranali; Nikumbh, Milind. B.; Dawre, Manisha. K.; Rathod, Sanjay. T. (International Journal of Ayurveda and Pharma Research, 2017)
Ayurveda is one of the most reliable and complete medical science. The union of Mamsa, Sira, Snayu Asthi and Sandhi are called as Marma. Acharya Sushruta stated every aspect of Marma like definition, signs and symptoms of Marma injury. Total number of Marma as described in Samhitas are 107 in number. Marma science is one of the special aspects deeply elaborated by Ayurveda. Marma are several vital points on the body having importance regarding traumatic effect. These vital points when exposed to trauma generate the symptoms from pain to fatal effect. These points should be protected from injury. Detail knowledge of Marma is important from surgical point of view. Acharya Sushruta explain the Marma viddha lakshana in detail. Human body when expose to trauma shows various signs and symptoms depending on severity and type of trauma. when the trauma to the Kakshadhara Marma causes â€œErbs Palsyâ€. Erbs palsy is the paralysis of the arm caused by injury to the upper trunk (c5-c6) of the brachial plexus. There are other ancient Indian sciences also in which the vital points of human body are described. The main aim of this study is to understand the kakshadhra Marma, its location in human body, its applied aspect and to find out any similarity with the vital points explain in Ayurved classics.